ANALYSIS OF THE PARTICIPATION AND SIGNIFICANT ASPECTS OF COMMERCIAL BANKS IN THE FUND MARKET - Mardonov Shaxriyor Xolmirzo o‘g‘li (European Journal of Interdisciplinary Research and Development, 2023)
This article analyzes the participation of banks in the stock market and examines the financial capacity of commercial banks. In particular, their capitalization level, loan portfolio and deposit were analyzed. Also, the article highlights the opinions of foreign and local scientists on this matter, and the author formulates suggestions and recommendations on the topic.